2016
DOI: 10.21474/ijar01/965
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamines Regulate Vitellogenesis via Cross-Talks With Allatotrophe in the American Cockroach, Periplaneta Americana.

Abstract: Vitellogenesis in many insect species is triggered by juvenile hormone (JH) where other factors such as neural or endocrinological ones also play a important roles. Newly emerged adult females of the American cockroach, Periplaneta americana were injected with indoleamines such as tryptamine (Tn), N-acetyltryptamine (NATn), serotonin (5-HT), N-acetylserotonin (NAS) and melatonin (ME) at 20, 30 and 40 µg in the abdomen. Tn and NATn stimulated Vg synthesis, while 5-HT, NAS and ME inhibited it. These amines may e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Also in A. pernyi, melatonin and serotonin control the photoperiodic response by regulating the release/synthesis of PTTH (Wang et al 2013). In the cockroach Periplaneta americana, melatonin has been shown to inhibit vitellogenin synthesis in the fat body, which is usually associated with ovarian development (Kamruzzaman et al, 2016). Additionally, Kamruzzaman et al (2016) found that melatonin inhibits the expression of the genes JHAMT (Juvenile Hormone Acid O-MethylTransferase) and FAMet (Farnesoic Acid O-Methyltransferase) encoding enzymes involved in the synthesis of Juvenile Hormone (JH).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also in A. pernyi, melatonin and serotonin control the photoperiodic response by regulating the release/synthesis of PTTH (Wang et al 2013). In the cockroach Periplaneta americana, melatonin has been shown to inhibit vitellogenin synthesis in the fat body, which is usually associated with ovarian development (Kamruzzaman et al, 2016). Additionally, Kamruzzaman et al (2016) found that melatonin inhibits the expression of the genes JHAMT (Juvenile Hormone Acid O-MethylTransferase) and FAMet (Farnesoic Acid O-Methyltransferase) encoding enzymes involved in the synthesis of Juvenile Hormone (JH).…”
Section: Discussionmentioning
confidence: 99%
“…In the cockroach Periplaneta americana, melatonin has been shown to inhibit vitellogenin synthesis in the fat body, which is usually associated with ovarian development (Kamruzzaman et al, 2016). Additionally, Kamruzzaman et al (2016) found that melatonin inhibits the expression of the genes JHAMT (Juvenile Hormone Acid O-MethylTransferase) and FAMet (Farnesoic Acid O-Methyltransferase) encoding enzymes involved in the synthesis of Juvenile Hormone (JH). In this context it is worth noticing that JH is known to regulate diapause incidence in several insects (Denlinger et al, 2012;Goodman & Cusson, 2012), in addition to its roles in the regulation of development and the control of polyphenisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aaNAT transfers an acetyl moiety, a rate-limiting step, to indoleamines and other arylalkylamines including serotonin (5-hydroxytryptamine; 5-HT) to form N-acetylserotonin (NAS; normelatonin), a substrate for MEL synthesis [27]. We have shown that the injections of MEL, 5-HT, NAS, tryptamine (TN) and N-acetyltryptamine (NATN) significantly modified Vg synthesis and affected two JH-synthesizing enzymes, JHAMT and FAMeT [25,26]. aaNAT is highly expressed in the CNS, midgut and reproductive glands in P. americana [25,29].…”
Section: Introductionmentioning
confidence: 99%
“…The coordination between the reproductive and metabolic organs is vital for survival. Also, the JH/20E route and indoleamine route (see below) have been investigated independently [25,26] and the effects of CCAP/sNPF have been neither investigated directly nor in terms of allatotrophe's regulatory pathway. Disentangling such a complicated network of pathways acting in insect reproduction is important as it is not always clear to what degree functional data obtained in a given model species can be interpolated to other insect taxa because of the different life-history traits, developmental plasticity and the long evolutionary history of many insect orders [4,22].…”
Section: Introductionmentioning
confidence: 99%